Sistem Pendukung Keputusan Penentuan Karyawan Terbaik Pada PT. Dinakara Putra Menggunakan Metode Simple Additive Weighting (SAW) - Amalia Putri, Rizqiana; Hidayat, Rahmat (Jurnal Sistem Informasi Akuntansi, 2024)
Dinakara Putra is a business engaged in the plastic industry, producing various eco-friendly packaging products such as Oxium additive & Cassava Bag / Starch Bag for bread and medicine pouch packaging, as well as multilayer packaging like lid cups and standing pouches. The company selects the best employees based on their performance, and as an appreciation, bonuses are given to selected employees. However, the current evaluation system is conducted by one person and is subjective, lacking structure and consistency among evaluations. Therefore, there is a need for a decision support system to facilitate the company in accurately determining the best employeesThis research employs the Simple Additive Weighting (SAW) method for decision-making, which calculates the total weight of performance assessments for each alternative across all relevant attributes. Data collection methods include observation, interviews, and literature review with a waterfall resolution method. There are 4 weighted criteria evaluated: attendance 20%, work quality 30%, cooperation 25%, and responsibility 25%. Based on the calculated results, the top employee with the highest score according to the established criteria at PT. Dinakara